The Role Of Leader In Work Addiction - Véghné Madarasi, Veronika; Barizsné Hadházi, Edit (International Journal of Engineering and Management Sciences, 2024)
Over-attachment to work is an increasingly common phenomenon in the lives of people in organisations, and can also be a condition of work addiction. Whoever becomes involved in an organisation, be it a subordinate or even a manager, work addiction has a number of negative consequences at both individual and organisational level. Without being exhaustive, work addiction can have an impact on organisational performance, organisational effectiveness, workplace conflict, career prospects, health maintenance. In this paper, we aim to highlight the most relevant publications from the last five years to report on the impact in an organisation when work addiction arises among subordinates or managers, and how different leadership styles are associated with work addiction among organisational members. The publications were retrieved from Google Scholar and Scopus, and the results of 19 articles are presented in this paper after a review of 263 papers retrieved. The results show that transformational, servant and ethical leadership styles have ambiguous effects on work addiction, unlike laissez-faire or abusive leadership styles, the former enhancing and the latter reducing the incidence of work addiction in an organisation. Work addiction of managers also has a dual effect: on the one hand, it can enhance creativity, but it can also increase turnover among subordinates. Social support from the manager can be an antidote to subordinates’ work addiction, but this effect may be modified by the quantity and quality of interaction between manager and subordinate, the sense of meaningfulness of the work, or even the organisational culture. Overall, the manager, as a key actor, can have an impact on work addiction in the organisation, but there is not always a consistent position in the research on the cases and the way in which this is done, which calls for further research in the future.